Risk factors, perceptions and practices associated with Taenia solium cysticercosis and its control in the smallholder pig production systems in Uganda: a cross-sectional survey. Issue 1 (December 2017) - Kungu, Joseph; Dione, Michel; Ejobi, Francis; Ocaido, Michael; Grace, Delia
Abstract Background Prevalence studies reportTaenia solium cysticercosis in pig and human populations in Uganda. However, the factors influencing occurrence in smallholder pig production systems are not well documented and little is known about farmers' perceptions ofT. solium cysticercosis or farmer practices that could reduce transmission. Methods To determine the risk factors, perceptions and practices regardingT. solium cysticercosis, a household survey using a semi-structured questionnaire was conducted in 1185 households in the rural and urban pig production systems in Masaka, Mukono and Kamuli Districts. Logistic regression was used to measure associations of risk factors with infection. Performance scores were calculated to summarise perceptions and practices of farmers regarding taeniosis, human cysticercosis and porcine cysticercosis as well as farmer behavior related to control or breaking transmission. Results Pig breed type, farmers' knowledge about transmission, sources of water used, and pig keeping homes where family members were unable to use the latrine were all significantly associated withT. solium cysticercosis in pigs. Performance scores indicated that farmers were more aware of taeniosis (63.0%; 95% Confidence Interval 60.0-65.8) than human or porcine cysticercosis; only three farmers (0.3%, 95% CI = 0.1–0.8) had knowledge on all three conditions. More farmers reported that they dewormed pigs (94.1%) than reported deworming themselves and their family members (62.0%). Albendazole was the most commonly used drug for deworming both pigs and humans (85.0 and 81.5% respectively). Just over half (54.6%) of the farmers interviewed had clean water near the latrines for washing hands. Of these, only 41.9% used water with soap to wash hands after latrine use. Conclusion Factors that significantly influenced occurrence ofT. solium cysticercosis in pigs were identified. Farmers had some knowledge about the disease but did not link taeniosis, human cysticercosis, and porcine cysticercosis. Therefore, there is need to employ strategies that raise awareness and interrupt transmission.